Komunikasi Krisis Pemerintah Kabupaten Batubara dalam Diseminasi Informasi Pelayanan Publik di Masa Pandemi Covid-19 - Arief Marizki Purba; Munzaimah Masril; Nana Dyki Dirbawanto (Journal of Social and Policy Issues, 2023)
One of the main problems caused by Covid-19 is the problem of communication, especially in controlling so that the virus does not spread quickly. The regional government of Batubara Regency, North Sumatra Province, is required to be able to make top-down policy adjustments from the central government to policies issued by the regional government in order to overcome the spread of the virus. The problem is the amount of information circulating in the community which makes it difficult to optimally handle Covid-19 in an area. Apart from disinformation about Covid-19 and vaccines, changes to Methode's policy were made by the government to anticipate the spread of the virus. This means that in a crisis situation like this the role of Public Relations from the Regional Government is very important in providing accurate and reliable information in order to gain public trust. This research is qualitative research with descriptive analysis. The purpose of this study is to explain the Crisis Communication of the Batubara District Government in Socializing Public Services During the Covid-19 Pandemic. The results of this study explain the Challenges of Handling Hoaxes in a Pandemic. The conclusion of this study explains the Sense of Crisis in conveying Information and Dissemination of Information regarding the spread of Covid-19. This research is the result of original research conducted by researchers in 2022.